Corporate governance best practices : strategies for public, private, and not-for-profit organizations - Lipman, Frederick D.; Lipman, L. Keith, 1967- (Hoboken, N.J. : Wiley, 2006)
This book outlines best practices for board directors in public, private, and not-for-profit organizations. It provides real-world cases and best practices in corporate culture, compliance, audit committees, compensation committees, other committees, working with internal audit, IT corporate governance, as well as other board responsibilities.
Why is corporate governance important? -- Summary of major corporate governance principles and best practices -- Best practices to monitor risk in different organizational departments -- Monitoring and changing the corporate culture -- The internal audit function -- Compensation committees of public, private, and not-for-profit organizations -- Other committees -- Independent directors and their committees -- IT content: best corporate governance practices -- IT security best corporate governance practices -- Who can qualify for a public company audit committee? -- Public company audit committee: personal liability of audit committee members -- Minimum responsibilities of public company audit committees -- Other public company audit committee functions -- 30 best practice considerations for the public company audit committee -- Who is an independent auditor? -- Corporate governance for family-owned and other private businesses -- Corporate governance for not-for-profit organizations.
Series from jacket.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Corporate governance; Gouvernement d'entreprise.; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; Corporate governance; Corporate governance; Corporate Governance; Bedrijfsbeleid; Corporate governance; Fallstudiensammlung